(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the problem of life satisfaction as a generalized assessment of the quality of a person’s existence. A theoretical and methodological review of modern concepts of the phenomenon is presented. An attempt is made of a detailed definitive analysis of the concept of “satisfaction with life” in a system of related categories. The specificity of this assessment is determined, namely, as an integral indicator of positive functioning. Some features of the structural model of satisfaction with life are revealed, in particular, the role of cognitive and emotional components in the processes of consolidation and constructivization of positive existential experiences of a person. The system of factors that phenomenalize emotionally — evaluative attitude to their life realization is allocated.